Exploration of Civic Education in the K-12 Christian School Environment. Issue 1 (2nd January 2021) - Lin, Alex R.
Abstract: With nationwide concerns about the declines in youth voting turnout across the United States, increased attention has focused on schools to promote civic education, a broad curricular approach aimed at facilitating students' development of key civic knowledge, skills, and behaviors. However, less is known about how civic education operates in K-12 Christian schools despite offering certain institutional advantages related to promoting strong relational trust and community values that can potentially enhance students' civic education experience. This literature review draws on theoretical and empirical work to provide an enhanced understanding about civic education in the Christian school context so that policymakers and practitioners can embrace the effectiveness of this blended approach to better preparing youth to become active and informed citizens.